Church Dedications in Badenoch and Strathspey Revisited - Bardgett, Frank D. (Scottish church history, 2021)
The article takes its start from Prof. G. Barrow's 1988-9' Badenochand Strathspey, 1130-1312. 2: The Church', and looks again at the evidence for pre-parochial dedications to saints in the light of recent archaeology and historiography. Strong ecclesiastical affinity with an Irish or Gaelic style of Christianity can be observed. Different options for a Sitz im Leben for this Gaelic connection are discussed and the eighth century is proposed as a plausible context for when the dedications in this region developed. No account of the conversion of the region is attempted. Whatever the state of the church before the battle of Dun Nechtain in 685, thereafter the kings of Fortriu, a Pictish realm and hegemony with increasing Gaelic characteristics, relied heavily on the Gaelic churches of Argyll, Perthshire and Atholl to structure and resource Christianity in this area of their kingdom. Yet if resources came from the south, control was based to the north, where centres of power have been identified at Portmahomack,Rosemarkie, Burghead and Kinneddar.